A CASE REPORT OF COMPLETE SEPARATION OF LOWER CERVICAL SPINE: A RARE PRESENTATION OF ‘UNDERTAKER’S FRACTURE’ (Journal of Forensic Medicine & Toxicology, 2023)
‘Undertaker’s fracture’ is the subluxation of the lower cervical spine, due to tear of the inter-vertebral disc at C6-C7 levels. It is usually produced due to rough handling of a dead body by mortuary attendants or during improper transportation. Here we are presenting the case of a decomposed dead body, unknown female, aged about 35- 40 years, recovered from the Narmada canal in June month. We found ‘Undertaker’s Fracture’ in the form of complete separation of cervical spine at the level of intervertebral disc between C6 and C7 vertebrae. No antemortem injuries were found. Post-mortem artefacts can mislead the autopsy surgeon with insufficient autopsy experience and even can lead to a miscarriage of justice. A good autopsy surgeon should be able to differentiate between a genuine autopsy finding and an artefact.
Keywords: Undertaker’s fracture; Post-mortem artefact; Decomposition.